Pengaruh Swamedikasi Penyakit Kulit terhadap Tingkat Pengetahuan Siswa di Panti Asuhan Yatim Muhammadiyah Kabupaten Pekalongan - Wulan Agustin Ningrum; Muhammad Mahruj Awaludin; Irma Suryani (Universitas Hamzanwadi, 2024)
Skin disease is one of the many diseases that is still a problem in the world, including Indonesia. This fungal skin disease is not fatal, however, because it is chronic and residual, and many people are resistant to the use of antifungal drugs. In this day and age, accessing information related to medicines is easier, so many people choose to take self-medication even though the implementation can cause errors. The number of cases of self-medication for skin diseases carried out by respondents in Muhammadiyah Orphanages throughout Pekalongan Regency. The aim of this research is to determine the level of students' knowledge of self-medication among respondents in Muhammadiyah Orphanages throughout Pekalongan Regency, consisting of Pekajangan, Kedungwuni, Wuled orphanages. , Wonopringgo, and Kajen. The method used in this research is an analytical survey with a cross sectional design. The sampling technique uses total sampling. The sample for this study was 75 respondents, namely respondents who had a history of skin disease and had done self-medication. The research results showed that 86,7% of respondents had a level of knowledge in the very good category. It can be concluded from the research that students at the Pekalongan Regency Muhammadiyah Orphanage have very good knowledge in self-treatment of skin diseases. More in-depth research needs to be done so that we can find out the relationship.